Analisis dan Solusi Kesulitan Belajar dalam Pendidikan Islam: Perspektif Al-Qur'an - Fitria, Yenni; Fitriani, Wahidah (Itqan: Jurnal Ilmu-ilmu Kependidikan, 2023)
This research aims to identify the various forms of learning difficulties experienced by learners and present solutions inspired by Qur'anic teachings to overcome these problems. This research used a literature study which involved collecting data through searching and reviewing relevant literature. Literature sources were selected based on inclusion and exclusion criteria. The data analysis process involved summarizing the data, presenting relevant data, and drawing conclusions. The results of the study suggest: 1) Learning difficulties in the Islamic view are influenced by internal (physical and spiritual aspects) and external (environmental situations and conditions) factors. Learning difficulties are classified based on criteria such as the type of difficulty, the field of study affected, the nature of the difficulty, and the factors causing it. 2) To overcome learning difficulties, the solutions exemplified in the Qur'an include increasing the motivation of learners, selecting appropriate learning methods, services that focus on the differences of learners, providing examples of stories and teachings that show the importance of the process of seeking knowledge. In addition, educators are expected to recognize the characteristics and learning styles of learners, provide services that are appropriate to differences, and be good role models. Thus, learning difficulties in the Islamic context are not only an individual problem, but also include external factors and require a holistic approach.